2014
DOI: 10.1155/2014/271918
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Nitric Oxide as a Biomarker in COPD and Related Comorbidities

Abstract: Chronic Obstructive Pulmonary Disease (COPD) is defined as a disease characterized by persistent, progressive airflow limitation. Recent studies have underlined that COPD is correlated to many systemic manifestations, probably due to an underlying pattern of systemic inflammation. In COPD fractional exhaled Nitric Oxide (FeNO) levels are related to smoking habits and disease severity, showing a positive relationship with respiratory functional parameters. Moreover FeNO is increased in patients with COPD exacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
67
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 78 publications
(88 reference statements)
1
67
3
2
Order By: Relevance
“…Our study reveals that before treatment the FeNO levels of patients with psoriasis are higher than normal, so the presence of subclinical active airway inflammation could be a risk factor linked to the possibility of developing COPD …”
Section: Patient Characteristicsmentioning
confidence: 78%
See 1 more Smart Citation
“…Our study reveals that before treatment the FeNO levels of patients with psoriasis are higher than normal, so the presence of subclinical active airway inflammation could be a risk factor linked to the possibility of developing COPD …”
Section: Patient Characteristicsmentioning
confidence: 78%
“…Inflammation can further increase the amount of NO by implementing iNOS expression. Thus, fractional exhaled NO (FeNO) has been accepted in the literature as an indirect marker of airway inflammation, and is currently used in the clinical monitoring and management of asthma inflammation levels …”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The fraction of exhaled nitric oxide (FeNO) levels in COPD patients is affected by smoking and disease severity. FeNO elevation in psoriasis patients may increase the risk of COPD [13] . A recent study found that FeNO levels were elevated in patients with psoriasis, possibly reflecting subclinical airway inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore designed a longitudinal panel study to explore the effects of O x on respiratory inflammation in a group of patients with chronic obstructive pulmonary disease (COPD) in Shanghai, China. Respiratory inflammation was evaluated using fractional exhaled nitric oxide (FeNO), a non-invasive biomarker commonly used in previous studies (Liu et al 2009, Malerba et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The X-axis refers to the categorization; the Y-axis refers to the percent changes in FeNO. Abbreviations: FeNO, fractional exhaled nitric oxide; BMI, body mass index Malerba et al 2014)…”
mentioning
confidence: 99%